2002
DOI: 10.1055/s-2002-36336
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of the Essential Oil ofAlpinia zerumbetLeaves and its Main Constituent, Terpinen-4-ol, in Rats: Role of the Autonomic Nervous System

Abstract: Cardiovascular effects of intravenous ( i. v.) treatment with the essential oil of Alpinia zerumbet (EOAZ) were investigated in rats. Additionally this study examined (I) whether the autonomic nervous system is involved in the mediation of EOAZ-induced changes in mean aortic pressure (MAP) and heart rate (HR), and (II) whether these changes could be, at least in part, attributed to the actions of terpinen-4-ol (Trp-4-ol), the major constituent of EOAZ. In both pentobarbitone-anaesthetised and conscious rats, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 12 publications
3
48
1
4
Order By: Relevance
“…Additionally, blood pressure reduction was higher in magnitude in SHR than in normotensive animals (p < .01) at all doses of EEAP, and in all but the two weakest doses of the IAP. Several studies have shown a blood pressure-lowering effect of AZ, a species very similar to AP (Mendonça et al, 1991;Mpalatinos et al, 1998;Lahlou et al, 2002Lahlou et al, , 2003De Moura et al, 2005;Barcelos et al, 2010). The study by Mendonça et al (1991) demonstrated an important blood pressure-lowering effect of the alcoholic extract of AZ in rats.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, blood pressure reduction was higher in magnitude in SHR than in normotensive animals (p < .01) at all doses of EEAP, and in all but the two weakest doses of the IAP. Several studies have shown a blood pressure-lowering effect of AZ, a species very similar to AP (Mendonça et al, 1991;Mpalatinos et al, 1998;Lahlou et al, 2002Lahlou et al, , 2003De Moura et al, 2005;Barcelos et al, 2010). The study by Mendonça et al (1991) demonstrated an important blood pressure-lowering effect of the alcoholic extract of AZ in rats.…”
Section: Resultsmentioning
confidence: 98%
“…The study by Mendonça et al (1991) demonstrated an important blood pressure-lowering effect of the alcoholic extract of AZ in rats. Lahlou et al (2002) observed that i.v. treatment with the essential oil of AZ induces immediate and significant hypotension in rats.…”
Section: Resultsmentioning
confidence: 99%
“…The acute intravenous administration of different extract of B. vulgaris (BRE, BRD) as well as Ach used as positive reference drug (Lahlou et al, 2002) in this study, all exerted immediate and significant fall in systolic, diastolic and mean arterial blood pressure (MABP) in normotensive anaesthetized rats.…”
Section: Discussionmentioning
confidence: 94%
“…É indicada principalmente no tratamento da hipertensão e da ansiedade (Matos, 2002); porém, outras propriedades lhe são mencionadas: diurética, estimulante do peristaltismo intestinal, emenagoga, antiulcerogênica, ação expectorante, usada em afecções respiratórias, intestinais e renais, amigdalite, faringite, rouquidão, reumatismo, nevralgia e dores lombares e musculares (Côrrea, 1974;Alice et al, 1995;Panizza, 1997). Em virtude disso, a espécie tornou-se referência de várias pesquisas (Bezerra et al, 2000;Chaves, 2001;Lahlou et al, 2002).…”
Section: Introductionunclassified
“…O terpinen-4-ol é considerado o principal constituinte químico do óleo essencial de A. zerumbet (Lahlou et al, 2002). Usando a ressonância magnética nuclear ( 13 C-NMR) como técnica de identificação complementar na análise de óleo essencial de A. zerumbet, Alencar et al (1997) identificaram ρ-cimeno (33,1%), 1,8-cineol (18,9%), (Ε)-terpinen-4-ol (18,8%) e sabineno (8,2%) como os constituintes em maior proporção.…”
Section: Introductionunclassified